Results of a survey of cancer patients' willingness to travel to participate in a clinical trial. Issue 10 (10th October 2019) - Zdenkowski, Nicholas; Lynam, James; Sproule, Victoria; Wall, Laura; Searston, Jessica; Brown, Scott
Abstract: Only 2–3% of cancer patients enrol in a trial. We surveyed patients' willingness to change clinician or treating centre, or to travel, to participate in trials, to improve trial recruitment. Of 188 respondents, 79% were willing to participate in a trial in at least one scenario. Increasing travel time, change in oncologist, private health insurance and out of pocket expenses decreased likelihood of joining a trial. Rural and regional patients, and those from lower socio‐economic areas, were more willing to travel. To optimise access to trials, clinicians should refer within and between institutions.